Validation of the Mechanism of Action of Jiedu Shengji Oil in the Treatment of Radiation Dermatitis based on Network Pharmacology and In Vivo Experiments - He, Weishan; Deng, Guangmei; Liu, Wenya; Kou, Long; Wu, Fasheng (Current computer-aided drug design, 2025)
Radiation Dermatitis (RD) is a common complication of radiation therapy, with approximately 90% of patients experiencing moderate to severe radiation dermatitis injury after radiotherapy. Jiedu Shengji oil (JDSJY) is a commonly used herbal topical preparation in our hospital, with remarkable clinical efficacy in treating radiation dermatitis. However, the mechanism of JDSJY in treating RD is unclear. The aim of the study is to explore JDSJY's mechanism of action in treating RD through methods, such as network pharmacology and in vivo experiments. The active components and disease targets of JDSJY were screened and intersected via network pharmacology for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. The pharmacodynamics of JDSJY was evaluated by establishing a rat model of RD. Network pharmacology showed that the pathway network of JDSJY action involved 64 targets and 6 pathways and might act by targeting key targets, such as C-reactive protein (CRP) and regulating the MAPK signalling pathway. In addition, in vivo experiments showed that JDSJY reduced skin inflammation and inhibited apoptosis, significantly ameliorated mitochondrial damage in keratinocytes, and reduced the levels of antioxidant-related indicators. Comprehensive network pharmacology and in vivo experiments revealed that JDSJY's therapeutic efficacy in RD is mediated by ameliorating oxidative stress and maintaining mitochondrial homeostasis in keratinocytes.